2014
DOI: 10.1002/jbm.a.35099
|View full text |Cite
|
Sign up to set email alerts
|

Microparticulated and nanoparticulated zirconium oxide added to calcium silicate cement: Evaluation of physicochemical and biological properties

Abstract: The physicochemical and biological properties of calcium silicate-based cement (CS) associated to microparticulated (micro) or nanoparticulated (nano) zirconium oxide (ZrO 2 ) were compared with CS and bismuth oxide (BO) with CS. The pH, release of calcium ions, radiopacity, setting time, and compression strength of the materials were evaluated. The tissue reaction promoted by these materials in the subcutaneous was also investigated by morphological, immunohistochemical, and quantitative analyses. For this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 34 publications
4
100
2
3
Order By: Relevance
“…Silva et al . () revealed better biological response to zirconium oxide than bismuth oxide added to PC in rat connective tissue. Other investigation in animals compared the effects of PC with iodoform and zirconium oxide, and morphological analysis revealed that groups including radio pacifying agents showed lower inflammation than pure PC group (Lourenço‐Neto et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silva et al . () revealed better biological response to zirconium oxide than bismuth oxide added to PC in rat connective tissue. Other investigation in animals compared the effects of PC with iodoform and zirconium oxide, and morphological analysis revealed that groups including radio pacifying agents showed lower inflammation than pure PC group (Lourenço‐Neto et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Iodoform seems to be harmless to connective tissue and it is widely available to clinicians (de Morais et al, 2006;Bortoluzzi et al, 2009). Another tested radiopacifier, zirconium oxide does not affect tissue integrity (Lourenço-Neto et al, 2014;Silva et al, 2014), and furthermore, preserves PC properties (Bortoluzzi et al, 2009;Húngaro-Duarte et al, 2009;Camilleri et al, 2011;Cutajar et al, 2011;Guerreiro-Tanomaru et al, 2012;Weckwerth et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six samples, with 10 mm diameter by 1.0 mm thickness, of each group were subjected to the radiopacity test [14, 25]. After the mixing of the materials, they were stored in 100% humidity at 37°C for 48 hours to set.…”
Section: Methodsmentioning
confidence: 99%
“…(HOLLAND, et al, 2001a;DUARTE, et al, 2003;MAROTO, et al, 2005;DREGER, et al, 2012 (SANTOS, et al, 2005;CAMILLERI, 2007CAMILLERI, ,2008c. Os altos níveis de pH são, geralmente, verificados nos períodos iniciais, antes da completa presa dos cimentos, sendo o mesmo verificado no estudo, corroborando com outros estudos (DUARTE, et al, 2003;DE VASCONCELOS, et al, 2009;VIVAN, et al, 2010;SILVA, et al, 2014). O nível do pH diminuiu com o tempo, porém se manteve alcalino.…”
Section: Cimento Portland Com 50% De Tungstato De Cálciounclassified